REVIVING EDUCATION IN NIGERIA FOR SUSTAINABLE ECONOMIC GROWTH: ISSUES, PROBLEMS AND PROSPECTS - Lasbrey, Anochiwa .I.; Uma, Kalu, E; Aniagolu, Hyacinth N; Ogbonna, B. M (PEOPLE: International Journal of Social Sciences, 2016)
Education has been identified as a critical agent in the development of a modern society because it plays a pivotal role in training and building human capacity for the nation. It is argued “as information grows exponentially, and its incorporation in the production process becomes increasing complex, the ability to absorb, and adapt new knowledge is determined by the nature, quality and quantity of the education system”. Nigerian government played the „Ostrich‟ while its educational system headed for a total collapse. This paper in a quest to examining the issues pertaining to the decay, finds poor funding, limited access to good education, obsolete curricula, brain drain, corruption, incessant University strikes, examination malpractice, inept leadership, and poor budgetary allocation to education as part of the problem. Our simple regression findings show a positive relationship between education, health and economic growth. Therefore, except the system is revived and revamped, it will be a mirage for the country to catch up with the global competitiveness. As a way forward, Government must increase funding, tackle corruption and improve infrastructure. Excellence must be rewarded and indigenous R&D improved. They must stem the tide of brain drain by creating environment for good education.